Bibliometric Analysis of Pedagogical Content Knowledge (PCK) Publication Trends in Scopus Database from 2018 to 2022 - Muh. Alka; Hartono Bancong; Muhammad Muzaini; Sukmawati; Ernawati (Indonesia Approach Education, 2023)
This study aims to determine the research development with Pedagogical Content Knowledge in the World from 2018 to 2022. This research is a type of qualitative research with literature studies. Research data was obtained using the Scopus search engine to identify research related to the Pedagogical Content Knowledge theme from 2018 to 2022. This study also used the VOS viewer to map and analyze data. The findings in this study are that 2020 is the highest year in research publications. The United States is the country that contributes the most research publications. Furthermore, topics regarding content knowledge, students, and teaching, which have great opportunities for further research, are related to the theme of Pedagogical Content Knowledge. Content knowledge (students or teachers) is the most important topic in scientific research publications with the theme of Pedagogical Content Knowledge from 2018 to 2022 indexed by Scopus.